Analisis Sistematis Pengaruh Hybrid Learning Berbantuan Google Classroom Terhadap Pemahaman dan Pemecahan Masalah - Islawati, Islawati; Samsuddin, Yati Bt (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to evaluate the effectiveness of Hybrid Learning in enhancing students’ conceptual understanding and problem-solving skills. The research method employed is a Systematic Literature Review (SLR), analyzing nine studies published in accredited journals relevant to technology-based learning. Data sources were obtained from national and international journals discussing the implementation of Hybrid Learning, particularly those utilizing Google Classroom. The data analysis technique involved identification, screening, critical evaluation, and synthesis of findings from each study to gain a comprehensive understanding of the effectiveness of this approach on student learning outcomes. The findings indicate that Hybrid Learning provides flexibility in the learning process, allowing students to access materials anytime while enhancing their critical thinking and problem-solving skills. Additionally, the implementation of Google Classroom facilitates better interaction between students and teachers, thereby increasing learning motivation. The study also found that combining Hybrid Learning with Problem-Based Learning (PBL) yields more significant improvements in problem-solving skills compared to conventional methods. In conclusion, Hybrid Learning supported by Google Classroom is an effective teaching strategy and is recommended for implementation across various educational levels to improve the quality of technology-based learning.